Investigating the Association Between Seven Sleep Traits and Nonalcoholic Fatty Liver Disease: Observational and Mendelian Randomization Study - Fan, Hong; Liu, Zhenqiu; Zhang, Xin; Yuan, Huangbo; Zhao, Xiaolan; Zhao, Renjia; Shi, Tingting; Wu, Sheng; Xu, Yiyun; Suo, Chen; Chen, Xingdong; Zhang, Tiejun (Frontiers in Genetics, 2022)
Background and Aim: Aberrant sleep parameters are associated with the risk of nonalcoholic fatty liver disease (NAFLD). However, existing information is inconsistent among studies and involves reverse causation. Therefore, we aimed to investigate the observational associations and causations between sleep traits and NAFLD. Methods: We performed multivariable regression to assess observational associations of seven sleep traits (sleep duration, easiness of getting up in the morning, chronotype, nap during day, snoring, insomnia, and narcolepsy), and NAFLD in the UK Biobank (1,029 NAFLD). The Cox proportional hazards model was applied to derive hazard ratios and 95% confidence intervals (CIs). Furthermore, a bi-directional two-sample Mendelian randomization (MR) approach was used to explore the causal relationships between sleep traits and NAFLD. Results: In the multivariable regression model adjusted for potential confounders, getting up in the morning not at all easy (HR, 1.51; 95%CI, 1.27–1.78) and usually insomnia (HR, 1.46; 95%CI, 1.21–1.75) were associated with the risk of NAFLD. Furthermore, the easiness of getting up in the morning and insomnia showed a dose-response association with NAFLD (Ptrend<0.05). MR analysis found consistent causal effects of NAFLD on easiness of getting up in the morning (OR, 0.995; 95%CI, 0.990–0.999; P = 0.033) and insomnia (OR, 1.006; 95%CI, 1.001–1.011; P=0.024). These results were robust to weak instrument bias, pleiotropy, and heterogeneity. Conclusions: Findings showed consistent evidence of observational analyses and MR analyses that trouble getting up in morning and insomnia were associated with an increased risk of NAFLD. Bi-directional MR demonstrated causal effects of NAFLD on sleep traits.